Strategic marketing management : eeting the global marketing challenge - Anderson, Carol H.; Vincze, Julian W. (Boston : Houghton Mifflin, 2000)
This book is about: An introduction to strategic marketing management; Achieving competitive advantage; Implementing marketing-Mix strategies; Managing marketing efforts; ...
Keywords: Marketing; Management; Strategic planning; Strategic planning; Marketing -- Management